Turkey : Report on Observance of Standards and Codes; Data Module, Response by the Authorities, and Detailed Assessment Using the Data Quality Assessment Framework (DQAF). (IMF Staff Country Reports; Country Report ;, 2009)
This report examines the Observance of Standards and Codes on the Data Module for Turkey. Progress in data quality reflects the authorities' commitment to set statistical development on a high and sustainable path, and to address remaining challenges. A cornerstone of this effort is the more robust framework established by the new Statistics Law of Turkey of November 2005. This law assigned compilation responsibilities for a broad range of official data, including macroeconomic statistics.